Effect of Drying Time on Chemical and Sensory Characteristics of Nutmeg Peel Herbal Tea (Myristica fragrans Houtt) - Sinthia H Latarissa; Rachel Breemer; Syane Palijama (Jurnal Agrosilvopasture-Tech, 2022)
s study aims to study the effect of drying time on the chemical and sensory properties of nutmeg peel herbal tea. This study was developed using a single factor Completely Randomized Design (CRD) with 4 stages, namely drying time of 4, 5, 6, and 7 hours. The results showed that the drying time treatment had a significant effect on the observation parameters, namely the yield ranged from 42.55 to 54.97%, total phenol ranged from 12.55 to 14.56%, fiber content 57.48 to 65.40%, moisture content ranged from 9.47 to 12.71%, ash content ranged from 10.47 to 13.91. The results of the sensory test showed that the nutmeg skin herbal tea for the color parameter of the overall acceptance level was somewhat favored - favored by the panelists, for the aroma parameter the overall acceptance level was somewhat favored by the panelists and for the taste parameter the overall acceptance level was not favored - somewhat favored by the panelists.